The Effect of Sensory Integration Therapy on Improving The Writing Skills of Children with Special Needs - Putrie Widyana, Vanya; Sugiasih, Inhastuti (Universitas Islam Indonesia, 2025)
This study aimed to examine the effect of sensory integration therapy inimproving the writing skills of children with special needs at the N-Ergy Psychology Center.A qualitative experimental method was adopted, specifically a Single Subject Research (SSR)design with an A-B-A' pattern. The sample consisted of 3 children subjected to psychomotortherapy at the center. Data were collected using a tracing test, the Beery VMI, VisualPerception and Motor Coordination subtests, as well as handwriting observation. Analysiswas conducted visually and presented in the form of tables and graphs to reflect changes insubjects' behavior before, during, and after the intervention. The results showed animprovement in writing skills across all participants. Sample MAB had a mean score of 0.333in Phase A-1, which increased to 3.692 in Phase B, and 6 in Phase A-2. The mean score ofAFR increased from 4 in Phase A-1 to 8.077 in Phase B, and further to 13.33 in Phase A-2.SANA increased from 13 in Phase A-1 to 15.231 in Phase B, and slightly decreased to 14 inPhase A-2. In addition to improved tracing test scores, enhancements were also observed inthe Beery VMI scores, Visual Perception and Motor Coordination subtests, as well ashandwriting quality. These results suggest that sensory integration therapy has a positiveeffect on improving the writing skills of children with special needs. Therapy can beeffectively implemented in individualized settings in therapy institutions by providingappropriate sensory stimulation and engaging parents actively to achieve optimal outcomes.